New Paradigms: Development Learning Activities in the Classroom to Service Learning for Pre-Service Science Teachers Lampang Rajabhat University - Duangjan kaewkongpan; Chisapath Choothong; Lamay Junthakhao (Journal of Humanities and Social Sciences Mahasarakham University, 2021)
The aims of this study were to 1) develop the creativity of learning from classroom towards social services for pre-service science teachers, 2) study teamwork skills of pre-service science teachers and 3) study the satisfaction of pre-service science teachers of creativity of learning from classroom towards social services for pre-service science teacher. The target group were 57 second-year and third-year students selected by purposive sampling. The researcher used purposive sampling because they want pre-service science teachers to promote and develop the teaching techniques in the classroom towards social services. Qualitative data analysis was by the phenomenon explanation through the reflection of the learner, recording images via a camera phone, small group seminar, summarize and the learning lessons. Quantitative data analysis used descriptive statistics including mean and standard deviation. The tools used in the research consisted of:-1) a learning management plan of the creativity of learning from class room towards social services for pre-service science teacher, 2) creativity observation form, 3) interview form about team working behaviors, and 4) satisfaction questionnaire. The activities of the creativity of learning from classroom towards social services divided into 3 processes as follows; preparing process, action process, and reflection process. Pre-service science teachers achieved the knowledge, direct experiences of team working, life learning skills, communication skills, the characteristic development of being at eacher by doing, and linking the major subjects and professional teaching to further applications. The overall picture of satisfaction about learning activities in the classroom towards social service for pre-science teacher was in the high level.